Randomized clinical trial of intraoperative dexmedetomidine to prevent delirium in the elderly undergoing major non‐cardiac surgery - Li, C.‐J.; Wang, B.‐J.; Mu, D.‐L.; Hu, J.; Guo, C.; Li, X.‐Y.; Ma, D.; Wang, D.‐X. (British journal of surgery, 2020)
Background Delirium is common in elderly patients after surgery and is associated with poor outcomes. This study aimed to investigate the impact of intraoperative dexmedetomidine on the incidence of delirium in elderly patients undergoing major surgery. Methods This was a randomized double‐blind placebo‐controlled trial. Elderly patients (aged 60 years or more) scheduled to undergo major non‐cardiac surgery were randomized into two groups. Patients in the intervention group received a loading dose of dexmedetomidine 0·6 μg/kg 10 min before induction of anaesthesia followed by a continuous infusion (0·5 μg per kg per h) until 1 h before the end of surgery. Patients in the control group received volume‐matched normal saline in the same schedule. The primary outcome was the incidence of delirium during the first 5 days after surgery. Delirium was assessed with the Confusion Assessment Method (CAM) for non‐ventilated patients and CAM for the Intensive Care Unit for ventilated patients. Results In total, 309 patients who received dexmedetomidine and 310 control patients were included in the intention‐to‐treat analysis. The incidence of delirium within 5 days of surgery was lower with dexmedetomidine treatment: 5·5 per cent (17 of 309) versus 10·3 per cent (32 of 310) in the control group (relative risk (RR) 0·53, 95 per cent c.i. 0·30 to 0·94; P = 0·026). The overall incidence of complications at 30 days was also lower after dexmedetomidine (19·4 per cent (60 of 309) versus 26·1 per cent (81 of 310) for controls; RR 0·74, 0·55 to 0·99, P = 0·047). Conclusion Intraoperative dexmedetomidine halved the risk of delirium in the elderly after major non‐cardiac surgery. Registration number: ChiCTR‐IPR‐15007654 ( www.chictr.org.cn). Antecedentes El delirio después de la cirugía es frecuente en los pacientes de edad avanzada y se asocia con malos resultados. El objetivo de este estudio fue investigar el impacto de la administración intraoperatoria de dexmedetomidina en la incidencia de delirio en pacientes mayores sometidos a operaciones de cirugía mayor. Métodos Se trataba de un ensayo aleatorizado, doble ciego y controlado con placebo. Un total de 620 pacientes mayores (60 años o más) fueron programados para ser sometidos a intervenciones (no cardiacas) de cirugía mayor y se aleatorizaron a dos grupos. Los pacientes en el grupo de intervención recibieron una dosis de carga de dexmedetomidina (0,6 μg/kg, 10 minutos antes de la inducción anestésica) seguida de una infusión continua (0,5 μg/kg/h) hasta 1 h antes de la finalización de la cirugía. Los pacientes del grupo control recibieron el mismo volumen de suero salino siguiendo la misma pauta. El resultado principal era la incidencia de delirio durante los primeros 5 días postoperatorios. Para la valoración del delirio se utilizó el método para la evaluación de la confusión (Confusion Assessment Method, CAM) en pacientes no intubados y el CAM‐UCI para los pacientes intubados. Resultados En total, 309 pacientes que recibieron dexmedetomidina y 310 del grupo control se incluyeron en el análisis por intención de tratar. La incidencia de delirio durante los primeros 5 días tras la cirugía fue inferior en presencia de tratamiento con dexmedetomidina que en ausencia del mismo: 5,5% (17/309) versus 10,3% (32/310); riesgo relativo (RR) 0,53, i.c. del 95% 0,30‐0,94, P = 0,026. La incidencia global de complicaciones a los 30 días excluyendo el delirio también fue inferior en presencia que en ausencia de tratamiento con dexmedetomidina (19,4% (60/309) versus 26,1% (81/301), RR 0,74, i.c. del 95% 0,55‐0,99, P = 0,047). Conclusión La administración intraoperatoria de dexmedetomidina reduce la presencia de delirio en los pacientes mayores tras cirugía mayor no cardiaca. In this RCT, intraoperative infusion of dexmedetomidine was found to reduce the rate of postoperative delirium and surgery‐related complications. The shortcomings of previous studies, such as study design and sample size, were amended, providing more robust evidence for clinical practice. Halved the rate of delirium